How can traditional Chinese medicine trials achieve global credibility - Ying Wang; Gordon Guyatt (Evidence-Based Chinese Medicine and Technology Assessment, 2026)
Abstract Traditional Chinese medicine (TCM) needs credible evidence that meets international evidence-based medicine standards to achieve global credibility and acceptance. A fundamental and crucial task is to conduct high-quality randomized controlled trials (RCTs). To achieve global credibility, TCM RCTs should meet universal standards of scientific rigor, such as addressing clinically important questions, achieving sufficient sample size and minimizing risk of bias, and enhance generalizability through appropriate multicenter and pragmatic designs, including Western centers, populations and trialists. In addition, TCM RCTs face unique challenges. Addressing these challenges through rigorous trial methodology and TCM-specific methodological innovation will be essential for establishing globally credible evidence and facilitating the international integration of TCM.